Leishmanioses: estado da arte - Pereira, Ivan de Oliveira; Sacramento, Luis Vitor Silva do [UNESP]; Marques, Marcos José (Universidade Vale do Rio Verde (UninCor), 2011)
There is no vaccine available against leishmaniasis. Drug resistance, variable efficacy, toxicity, parenteral administration, and requirement for long courses of administration are the main drawbacks of current leishmanicidal drugs. Infections by protozoans of the genus Leishmania are the major worldwide health problem, with high endemicity in developing countries. The drugs of choice for the treatment of leishmaniasis are the pentavalent antimonials, which exert renal and cardiac toxicity, thus, there is a strong need for safer and more effective treatments against leishmaniasis.

Não há vacinas disponíveis contra leishmanioses. A resistências às drogas, eficácia variável, toxicidade, administração parenteral e a necessidade de longos períodos de tratamento representam os principais desafios das atuais drogas leishmanicidas. Infecções por protozoários do gênero Leishmania representam um grande problema de saúde, com alta endemicidade em paises em desenvolvimento. As drogas de escolha para o tratamento das leishmanioses são os antimoniais pentavalentes, que apresentam toxicidade renal e cardíaca, assim, existe uma grande necessidade de tratamentos contra leishmanioses mais seguros e efetivos.
Keywords: Leishmaniasis; Treatments; Leishmania; Leishmanioses; Tratamentos; Leishmania